Contemporary Quantitative Analysis of Events Such as Downgrading, Resizing and Declassification of Federalized Protected Areas in Brazil - Menezes, Glaucio Costa de; Fontgalland, Isabel Lausanne (International Journal of Global Sustainability, 2022)
This paper presents a contemporary analytical and quantitative study of protected area downgrading, downsizing, and degazettement-type events of federalized protected areas in Brazil. In view of its continental dimensions, it has faced strong pressures to build sustainable conservation standards, which culminated in a long and brilliant process of updating and perfecting its environmental legislation, considered one of the most modern in the world. However, due to the whims of the capitalist system, Brazil had to relinquish land within environmental preservation areas so road and hydroelectric infrastructure systems could be expanded to better serve the population. Faced with this scenario, some critical questions arise: how did the “Conservation Units” (UC’s) in Brazil originate? How many of these UCs are under federal governance? How many protected area downgrading, downsizing, and degazettement (PADDD) events of conservation areas have affected or influenced federal UCs? What are the primary provocative tendencies of these PADDD events? What can be suggested to minimize the effects of PADDD events on the existing UCs in the Brazilian territory? Employing bibliographic surveys and analysis of data related to the PADDD events in Brazil and on the federal UCs, provided by institutes involved in environmental preservation, we will arrive at the most satisfactory and coherent answers to the aforementioned questions.